Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1590/s0100-40422012000500020
|View full text |Cite
|
Sign up to set email alerts
|

Estudo químico de Sinningia allagophylla guiado por testes de atividade antiproliferativa

Abstract: Recebido em 18/9/11; aceito em 5/12/11; publicado na web em 28/2/12 CHEMICAL STUDY OF Sinningia allagophylla GUIDED BY ANTIPROLIFERATIVE ACTIVITY ASSAYS. Activity guided fractionation of Sinningia allagophylla (Mart.) Wiehler ethanolic extract yielded a new benzochromene 8-methoxylapachenol, besides seven known compounds: lapachenol, sitosteryl oleate, sitosteryl linoleate, stigmasteryl oleate, stigmasteryl linoleate, dunniol and tectoquinone. Extract, fractions, and compounds lapachenol, 8-methoxylapachenol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…Two olefinic protons (δ H 5.65, 6.55), one methoxy group (δ H 3.96), one hydroxymethylene group (δ H 3.70, 3.78), and one methyl group (δ H 1.42) were also observed. These data were very similar to those of lapachenole, reported from S. allagophylla 4 and reisolated in this work. In comparison with lapachenole, compound 1 differs by replacement of one methyl group at C-2 by a hydroxymethylene group.…”
Section: ■ Results and Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Two olefinic protons (δ H 5.65, 6.55), one methoxy group (δ H 3.96), one hydroxymethylene group (δ H 3.70, 3.78), and one methyl group (δ H 1.42) were also observed. These data were very similar to those of lapachenole, reported from S. allagophylla 4 and reisolated in this work. In comparison with lapachenole, compound 1 differs by replacement of one methyl group at C-2 by a hydroxymethylene group.…”
Section: ■ Results and Discussionsupporting
confidence: 92%
“…The 1 H NMR data of 3 (Table 2) showed signals for six aromatic protons in the spin systems of two 1,2,4trisubstituted aromatic moieties (δ H 7.13−8.13), three isolated protons (δ H 6.09, 6.36, and 6.58), four methoxy groups (δ H 3.82, 3.87, 3.93, and 3.94), four methyl groups (δ H 1.31, 1.55, 1.62, and 1.70), two diastereotopic methylene protons (δ H 1.99 and 2.22), and a benzylic proton (δ H 3.77). These data resembled those of 8-methoxylapachenole, 4 but the molecular mass and the duplication of several signals indicated a dimeric structure. The presence of benzylic and methylene protons suggested hydrogenation of an olefinic bond of the 2H-pyran ring.…”
Section: ■ Results and Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Our results resemble the study of Mazzio et al [34], which demonstrated that ethanolic extract of rhizomes of C. rotundus showed moderate anticancer activity in Neuro-2a cells (LC50 = 2.528 to 4.939 mg/mL calculated from dose-dependent cell death). Riva [35] tested the ethanolic extract of tubers of S. allagophylla against eight tumor cell lines, which presented a weak in vitro antiproliferative effect, except for the line of K-562 cells (leukemia), whose growth was completely inhibited with TGI concentration of 5.13 µg/mL (Figure 3). In summary, the major compounds identified in EECA belong to the sesquiterpenes group (e.g., isocorimbolone and mustakone) and demonstrated significant anti-proliferative activity against the tumor cell lines tested.…”
Section: Discussionmentioning
confidence: 99%
“…We are investigating this genus as part of a project of screening Brazilian Gesneriads, aiming at the isolation of new bioactive compounds. In previous studies we reported the isolation of cytotoxic and anti-inflammatory compounds from Sinningia allagophylla, 8,9 as well as cytotoxic and antinociceptive compounds from S. aggregatta. 10,11 Recently, a bioassay-guided fractionation led to the isolation of 7hydroxy-6-methoxy-α-dunnione, a naphthoquinone with antiinflammatory and antipyretic properties, from the less polar extracts of S. canescens tubers.…”
mentioning
confidence: 99%